Judicial Decision and Backlash from the Decisions of the Federal Supreme Court - Hoffmann, Grégora Beatriz (2021)
After certain considerations about the expansion of the Judiciary, judicialization, and activism in Brazil, followed by the analysis of decisions of the Federal Supreme Court that aused â€œbacklashâ€ effects, originated in the American constitutional law which means rejection of court decisions, it will be proposed a dialogue between the courts and the society in general as an instrument of the legitimacy of constitutional jurisdiction in the democratic order. This proposal will serve as an attempt to a possible strategy of democratic participation in decision making. The logic followed throughout this study is that dissent is a constitutive value in democratic societies and can only be reversed by improving the information process, which can be accomplished by facilitating its spread. In the structure and organization of the study, the methodology used will be hypothetical-deductive, based on the bibliographic research on the Federal Supreme Court.